Association of biomarkers and depressive symptoms in schizophrenia - Noto, Cristiano Souza [UNIFESP] (2011)
Emergence of depressive symptoms in schizophrenia results in a deteriorating course and poor prognosis. Schizophrenia and depressive disorder are both associated with low levels of brain-derived neurotrophic factor (BDNF) and with a longstanding low grade inflammatory state. the objective of this study is to analyze the relationship between these serum biomarkers and depressive and psychotic symptoms in schizophrenic patients. Thirty-nine individuals diagnosed with schizophrenia or schizoaffective disorder by Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), assessed by Structured Clinical Interview for DSM-IV (SCID), were included. Interviews were conducted with the Positive and Negative Syndrome Scale (PANSS) and the Calgary Depression Scale for Schizophrenia (CDSS). Blood samples were collected for determination of BDNF, IL-1 beta, IL-6, IL-8,1-10, IL-12 and TNF-alpha measurements. Positive correlations between BDNF and CDSS and between IL-1beta and severity in PANSS scores were found. BDNF levels were not correlated with any cytokine or with PANSS scores. the results of this study suggest that depressive and psychotic symptoms may be associated with different profiles of biomarkers in the association between schizophrenia and depression. (C) 2011 Elsevier Ireland Ltd. All rights reserved.